2018
DOI: 10.1186/s12911-018-0599-5
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine pharmacovigilance in signal detection: decision tree-based data classification

Abstract: BackgroundTraditional Chinese Medicine (TCM) is a style of traditional medicine informed by modern medicine but built on a foundation of more than 2500 years of Chinese medical practice. According to statistics, TCM accounts for approximately 14% of total adverse drug reaction (ADR) spontaneous reporting data in China. Because of the complexity of the components in TCM formula, which makes it essentially different from Western medicine, it is critical to determine whether ADR reports of TCM should be analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…e overall research idea is shown in Figure 4. Wei et al [64] selected the reports from the Chinese spontaneous report database from 2010 to 2011 and used a decision tree to calculate the classification of adverse drug reactions (ADR) signals. Tao Zheng et al [65] adopted a decision tree algorithm to construct a basic data framework.…”
Section: Gain Ratio (A S) � Gain(s A) Split Information(s A)mentioning
confidence: 99%
“…e overall research idea is shown in Figure 4. Wei et al [64] selected the reports from the Chinese spontaneous report database from 2010 to 2011 and used a decision tree to calculate the classification of adverse drug reactions (ADR) signals. Tao Zheng et al [65] adopted a decision tree algorithm to construct a basic data framework.…”
Section: Gain Ratio (A S) � Gain(s A) Split Information(s A)mentioning
confidence: 99%
“…We vertify our proposed model TPGen on a real-world dataset T LD, collected from lung cancer patients in clinic, and on a public dataset CKCEST [2] [8]. Our dataset consists of 10000+ TCM prescriptions targeted to lung cancer provided by the cooperative hospital.…”
Section: Datasetsmentioning
confidence: 99%
“…Our dataset consists of 10000+ TCM prescriptions targeted to lung cancer provided by the cooperative hospital. The number of the total sample is 10052, in which the dimension of input data, i.e., the symptom, is 189 and [2] https://github.com/yao8839836/PTM the number of the output labels, i.e., herbs, is 357. The statistics of the TCM datasets is summarized in Tab.…”
Section: Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies in China had attempted to use safety signalling tools to monitor THM products safety signal and are still refining their methods and databases. 9,10 There are no local studies in Malaysia investigating the trend of adulterated THM products and the potential use of safety signalling tools for THM products. Therefore, this present study aims to identify the trend of seized adulterated THM products in Malaysia and to assess the safety signalling of ARs associated with THM products.…”
Section: Introductionmentioning
confidence: 99%